A chemical method for identifying the photocatalytic active sites on carbon dots. (July 2016) - Hu, Shengliang; Zhang, Wenyu; Chang, Qing; Yang, Jinlong; Lin, Kui
Abstract: Fluorescent carbon dots (CDs) with oxygen-containing functional groups were prepared by a hydrothermal method. Three kinds of typical oxygen functional groups, i.e. hydroxyl, carbonyl, and carboxylic acid groups, were selectively deactivated to independently assess their photocatalytic activities on the surface of CDs. The presented results indicate that the carbonyl group on CDs is their photocatalytic active sites. Hereby, the high photocatalytic activities of CDs could be produced by enhancing carbonyl group concentration on their surface.